PUBLIC UNDERSTANDING OF THE WADI'AH AGREEMENT AND THE DECISION TO SAVE AT INDONESIAN SHARIA BANK - Ulfa, Fatonah; Albab, Ulil; Mawardi, Mawardi (widya balina, 2023)
This research aims to understand how the community comprehends the wadi'ah contract in the Indonesian Shariah Bank, Central Lampung Branch. The researcher employed a qualitative descriptive approach with data collection techniques, including observation, interviews, and documentation, to explore this issue comprehensively. The acquired data was analyzed using the analysis model and Spradly. The research findings revealed that the level of understanding among Indonesian Shariah Bank Central Lampung Branch customers is proficient. Proficiency can be interpreted as a level of knowledge that can be effectively used to explain what is known accurately. However, at this level of expertise, proficient individuals may only sometimes be able to apply what they understand in real-world situations. Therefore, it can be concluded that the Indonesian Shariah Bank, Central Lampung Branch customers, have a proficient understanding, as all 15 informants demonstrated a solid comprehension of the wadi'ah contract in the bank.